Media Pembelajaran Pengenalan Rumah Adat Berbasis Video dan Web pada Sekolah Dasar XYZ - Mesri M. Hutasoit; Liza Fitriana; David David (JITEKH, 2021)
Learning media has an important role in the student learning process. Seeing the declining student learning process, shows that students' understanding of the learning material is quite low. Media that is considered appropriate and in accordance with current conditions is learning media XYZ. Elementary School is one of the schools that is in the process of social studies learning media in the subject matter of Learning Media for the Introduction of Video and Web-Based Traditional Houses at XYZ Elementary Schools still using conventional methods of using textbooks and speeches so that students' attention is easily distracted because they are less attractive. learning methods. This has the impact that the students' lack of knowledge of the learning media for the introduction of traditional houses. if to overcome this problem the researcher makes learning media in the form of videos regarding learning materials for the introduction of traditional houses. With the existence of learning media for the introduction of traditional houses, it is easier for students to understand the lessons on introducing traditional houses using videos compared to the material provided by the teacher using the textbook reading method and lectures from the teacher.